The Determinants of Population Self-Control - Deborah A. Cobb-Clark; Sarah C. Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2022)
This paper demonstrates that structural factors can shape people's self-control. We study the determinants of adult self-control using population-representative data and exploiting two sources of quasi-experimental variation-Germany's division and compulsory schooling reforms. We find that former East Germans have substantially higher levels of self-control than West Germans and provide evidence for suppression as a possible underlying mechanism. An increase in compulsory schooling had no causal effect on self-control. Moreover, we find that self-control increases linearly with age. In contrast to previous findings for children, there is no gender gap in adult self-control and family background does not predict self-control.
Keywords: D90; C26; 330; population-representative evidence; Brief Self-Control Scale; determinants of self-control; German division; quasi-experiments; compulsory schooling reforms